Catalytic fast co-pyrolysis of biomass and food waste to produce aromatics: Analytical Py–GC/MS study. (August 2015) - Zhang, Bo; Zhong, Zhaoping; Min, Min; Ding, Kuan; Xie, Qinglong; Ruan, Roger
Highlights: We promoted the production of aromatics by catalytic fast co-pyrolysis process. Co-pyrolysis temperature of 600 °C was optimal for the formation of aromatics. Content of aromatics increased with increasing hydrogen to carbon effective ratio. There was an apparent synergistic effect between biomass and food waste. Abstract: In this study, catalytic fast co-pyrolysis (co-CFP) of corn stalk and food waste (FW) was carried out to produce aromatics using quantitative pyrolysis–gas chromatography/mass spectrometry (Py–GC/MS), and ZSM-5 zeolite in the hydrogen form was employed as the catalyst. Co-CFP temperature and a parameter called hydrogen to carbon effective ratio (H/Ceff ratio) were examined for their effects on the relative content of aromatics. Experimental results showed that co-CFP temperature of 600 °C was optimal for the formation of aromatics and other organic pyrolysis products. Besides, H/Ceff ratio had an important influence on product distribution. The yield of total organic pyrolysis products and relative content of aromatics increased non-linearly with increasing H/Ceff ratio. There was an apparent synergistic effect between corn stalk and FW during co-CFP process, which promoted the production of aromatics significantly. Co-CFP of biomass and FW was an effective method to produce aromatics and other petrochemicals.